O setor sucroenergético no Triângulo Mineiro (MG): crescimento econômico e manutenção das desigualdades sociais em municípios especializados - Stacciarini, João Henrique Santana (2019)
Understanding Brazil as a world leader in sugarcane production (641 million tons - 2017), the present work is devoted to the investigation of the contradictions existing in the process of activities expansion in the sugar-energy sector (production of sugar cane and by-products) in the Triângulo Mineiro, Minas Gerais state’s western portion, especially in what we are designating as specialized municipalities. In the last decades, especially in the period after the 2000s, a favorable set of circumstances, both national and international, contributed to the sector 's significant (re)appreciation. It is then within this context that the Triângulo Mineiro (MG), through a set of attributes, appears as a privileged space for the expansion of crops. However, if in the first moment the insertion of these new highly capitalized enterprises shows itself as a source of dynamization in economies and territorial logics, especially in less populous municipalities and more specialized in the activities of the sector, throughout time it is noted that, actually, these profits are extremely concentrated in the hands of those who control the territorial resources. Therefore, the sugar-energy activities, as they have been practiced in these specialized municipalities of the Triângulo Mineiro, are shown as socially excluding and spatially selective, leaving to the great part of the population the conviviality with the expansion of inequalities, poverty, vulnerability and dependency.